Dukungan Keluarga dengan Self-Management pada Pasien Hipertensi: Family Support with Self-Management in Hypertensive Patients - Robert Wicaksono; Puji Lestari (Journal of Holistics and Health Sciences, 2024)
Uncontrolled hypertension will cause complications. Management of hypertension must be done to reduce complications that will occur and must be carried out in the long term and continuously. Efforts to prevent these complications can be done with self-management. The implementation of hypertension self-management is influenced by several things such as health literacy, knowledge and family support. to determine the relationship between family support and self-management of hypertension. This research was a correlational research with a cross-sectional approach. The study population was hypertensive patients treated at RSUD dr. Gondo Suwarno, on average in one month as many as 48 patients. Samples are taken by accidental sampling. The data collection tool used a family support questionnaire and a Hypertension self-management behavior questionnaire (HSMBQ). Univariate analysis with frequency distribution tables, while bivariate analysis uses the Kendall Tau test. Family support was mostly in the good category by 18 respondents (37.5%) and hypertension self-management was mostly in the good category by 22 respondents (45.8%), the results of the kendall tau test obtained a p value of 0.001 with a correlation value of 0.420 which means there is a relationship Significantly enough between family support and self-management of hypertension at Dr.Gondo Suwarno Ungaran Hospital. It is expected that families provide support to people with hypertension so that they can motivate people with hypertension to improve self-management   ABSTRAK Hipertensi yang tidak terkontrol akan menyebabkan komplikasi. Penatalaksanaan hipertensi harus dilakukan untuk mengurangi komplikasi yang akan terjadi dan harus dilakukan dalam jangka yang panjang dan terus menerus.Upaya pencegahan komplikasi ini dapat dilakukan dengan self management. Pelaksanaan self management hipertensi ini dipengaruhi oleh beberapa hal seperti literasi kesehatan, pengetahuan dan dukungan keluarga. Untuk mengetahui hubungan dukungan keluarga dengan self management pada pasien hipertensi. Penelitian ini merupakan penelitian korelasional dengan pendekatan cross-sectional. Populasi penelitian adalah pasien hipertensi yang dirawat di RSUD dr. Gondo Suwarno, rata-rata dalam satu bulan sebanyak 48 pasien. Sampel diambil dengan accidental sampling. Alat pengumpulan data menggunakan kuesioner dukungan keluarga dan Hypertension self-management behavior questionnaire (HSMBQ). Analisa univariat dengan tabel distribusi frekuensi, sedangkan analisis bivariat menggunakan uji Kendall Tau Dukungan keluarga sebagian besar dalam kategori baik sebanyak 18 responden (37,5%) dan self-management hipertensi sebagian besar dalam kategori baik sebanyak 22 responden (45,8%), hasil uji kendall tau didapatkan p value 0,001 yang berarti ada hubungan signifikan antara dukungan keluarga dengan self-management hipertensi di RSUD dr.Gondo Suwarno Ungaran. Diharapkan keluarga memberikan dukungan pada penderita hipertensi sehingga dapat memotivasi penderita hipertensi untuk meningkatkan self-management